AWC Processing Tool: A geoprocessing workflow for adapting the Alaska Department of Fish and Game's Anadromous Waters Catalog for use in cultural landscape investigation. - Lim, J; Linares Matas, G (University of Oxford, 2022)
This tool is intended for use in ArcGIS Pro 2.7, and generates three shapefiles to help explore the relationship between Native Alaskan cultural landscapes, and salmonid activity in rivers. It does this by modifying the Alaska Anadromus Waters catalogue, available from: https://www.adfg.alaska.gov/sf/SARR/AWC/index.cfm?ADFG=maps.dataFiles